Clinical improvements in adopted children with fetal alcohol spectrum disorders through neurodevelopmentally informed clinical intervention: A pilot study. (October 2016) - Zarnegar, Zohreh; Hambrick, Erin P; Perry, Bruce D; Azen, Stanley P; Peterson, Cassandra
Research on early intervention for young children (infants and toddlers) with fetal alcohol spectrum disorders (FASD), particularly children with comorbid maltreatment experiences, is limited. Existing research has primarily focused on structuring environments to be responsive to the needs experienced by children with FASD rather than improving their functioning. The purpose of this study is to present outcomes from an early psychosocial intervention with 10 adopted, maltreated young children diagnosed with FASD, aged 10–53 months ( M  = 35 months), and their adoptive parents. The potential for early, targeted interventions to improve developmental outcomes for children with prenatal alcohol exposure was examined, as well as improving the skills of and reducing stress experienced by their adoptive parents. Based on the outcomes of a neurodevelopmentally informed assessment protocol, the 10 children whose data are presented were recommended to receive a range of regulatory, somatosensory, relational, and cognitive enrichments. As part of their treatment, children and caregivers received Child–Parent Psychotherapy (CPP), and caregivers (here, adoptive parents) also received Mindful Parenting Education (MPE). Related-samples Wilcoxon signed-rank tests indicated that scores of several measures of child developmental functioning improved from pre- to post-intervention and that parents' caregiving skills improved while their caregiving stress decreased. Reliable change analyses indicated that change observed from pre- to post-intervention was reliable. The promise of using neurodevelopmentally informed assessment strategies to sequence interventions for young children with diverse neurodevelopmental insults is discussed.